PENGARUH CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN (Studi KasusPT. Bintang Utara Perwakilan Dolok Sanggul) - Roy Parto Purba; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The company’s image is the impression of an object to another object that is formed by processing information at any time from various reliable sources .The company’s efforts as resources corporate image formation requires the presence of a complete. Datailed information is intended as information that can answer the needs and wants of the target object results corporate image can be extrinsic information guide for customers.This study aims to determine the influence of corporate image on customer loyalty ini PT.BINTANG UTARA bus Doloksanggul representaives as well as to examine the effect of these two variables. Meteologi in this research is descriptive and quantitative in SPSS, where samples were used that bus customers Bintang Utara Doloksanggul. To determine the sample using the formula slovin, with accidental sampling method sampling. Data collection through interviews and questionnaires.The results of the research corporate image of the four dimensions studied (characteristics, reputation, values and identity of the company) jointly showed a significant result on customer loyalty, which means dimensional image of the company significant effect on customer loyalty.Keywords : Company Image, Customer Loyalty, PT. Bintang Utara Doloksanggul. representative.